Adoption of AI-Enabled Tools in Social Development Organizations in India: An Extension of UTAUT Model - Jain, Ruchika; Garg, Naval; Khera, Shikha N. (Frontiers in Psychology, 2022)
Organizations increasingly use artificial intelligence (AI)-enabled tools to help teams work together. These tools substitute for various tasks and activities of team management. The employee's perception of AI can be crucial for adopting or avoiding tools. This study uses the unified theory of acceptance and use of technology (UTAUT) to identify factors influencing the use of AI-enabled tools by employees in organizations while assessing the role of aversion to AI. The model extended by evaluating the impact of these tools on the collaborative experience of employees in an organization. An online survey was distributed to employees working with AI-enabled tools. The analysis of the research model was conducted using partial least squares (PLS), with a two-step model–measurement and structural models of assessment. The results revealed that the antecedent variables- effort expectancy, performance expectancy, social influence, facilitating conditions and AI aversion effect the usage of AI-enabled tools. Also, social influence and facilitating conditions influenced the aversion of AI. The study also established a positive relationship between the use of AI-enabled tools and the collaborative experiences of employees. This study expands the antecedents by including factors beyond the UTAUT model. This study goes a step further to evaluate the impact of using technology on employee perception of collaboration in organizations.